2020
DOI: 10.14238/sp22.4.2020.252-60
|View full text |Cite
|
Sign up to set email alerts
|

Jadwal Imunisasi Anak Umur 0 – 18 tahun Rekomendasi Ikatan Dokter Anak Indonesia Tahun 2020

Abstract: Ikatan Dokter Anak Indonesia secara periodik mengkaji rekomendasi jadwal imunisasi untuk menyesuaikan dengan berbagai perkembangan yang terkait dengan jadwal imunisasi di Indonesia. Jadwal imunisasi 2020 ini bertujuan agar dapat digunakan oleh anggota IDAI dalam memenuhi keinginan masyarakat mendapatkan vaksin yang lebih lengkap. Perubahan pada  rekomendasi tahun 2020 adalah pada imunisasi Hepatitis B, IPV, BCG, DTP, Hib, Campak /MR/MMR, JE, Varicella, Hepatitis A dan Dengue.  Jadwal imunisasi lain tidak ada p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Diantara beberapa faktor tersebut pengetahuan ibu tentang imunisasi merupakan suatu faktor yang sangat erat hubungannya dengan status imunisasi anak (Soedjatmiko et al, 2020). Selain faktor sosio ekonomi keluarga, pelayanan kesehatan dan jumlah balita dalam keluarga juga ikut memberikan kontribusi terhadap status imunisasi bayi.…”
Section: Metode Penelitianunclassified
“…Diantara beberapa faktor tersebut pengetahuan ibu tentang imunisasi merupakan suatu faktor yang sangat erat hubungannya dengan status imunisasi anak (Soedjatmiko et al, 2020). Selain faktor sosio ekonomi keluarga, pelayanan kesehatan dan jumlah balita dalam keluarga juga ikut memberikan kontribusi terhadap status imunisasi bayi.…”
Section: Metode Penelitianunclassified
“…A Cochrane review found that rotavirus vaccination can prevent diarrhea (Soares-Weiser et al, 2019). IDAI stated that rotavirus vaccination can be given to children three times, at the ages of 2 months, 4 months, and 6 months (Soedjatmiko et al, 2020).…”
Section: Mapping Of Priority Areas Interventions For Toddler Diarrheamentioning
confidence: 99%
“…The immunization program must still be completed according to its schedule to protect children from Immunization Preventable Diseases (PD3I). 1 The postponement in the implementation of the BIAS program during the COVID-19 pandemic was due to the execution of online learning in the students' homes starting on the 18 th of May 2020, as stipulated by The Ministry of Education and Culture of the Republic of Indonesia (Kemendikbud RI) in order to prevent the transmission of COVID-19. 2,3 At the same time, measures to prevent other dangerous infectious diseases such as PD3I must continue through immunization to prevent Extraordinary Incidence (KLB) from happening.…”
Section: Introductionmentioning
confidence: 99%
“…4 Primary school-age children or their equivalents are the targets of the immunization program implemented in BIAS activities. 1 BIAS is a follow-up immunization program for primary schoolage children that is held twice a year and is run simultaneously in all districts/cities in Indonesia. It aims to provide protection against measles, diphtheria, and tetanus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation